ISLAMIC SPIRITUALITY AS THE FOUNDATION FOR THE CONTINUITY OF SILAT BUHUN SINGA DORANG IN PAMEUNGPEUK - Syahrial, Syahrial; Rahman, Irpan Ali; Nazarudin, Nazarudin (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
Silat as a traditional martial art has long evolved among various ethnic groups across the Nusantara archipelago, including the Sundanese, who have developed diverse schools of silat embedded within their cultural heritage. One such school, Silat Buhun Singa Dorang, later experienced a transformation into Pusaka Siliwangi. This study aims to investigate the socio-cultural and spiritual contexts underlying this renaming process and to elucidate the role of Islamic spirituality in sustaining the continuity of both Singa Dorang and Pusaka Siliwangi over time. Employing a qualitative research design within a modern ethnographic framework, this study relies on sensorybased engagement to collect rich, contextually grounded data that were analyzed and presented descriptively. The ethnographic approach is particularly appropriate, as the practice of Silat Buhun is deeply embedded in the socio-religious life of the Sundanese Muslim community in Pameungpeuk. The findings reveal that the transformation from Singa Dorang to Pusaka Siliwangi constitutes a deliberate recontextualization effort that aligns traditional martial values with Islamic ethical principles. This strategic rebranding not only reinforces the cultural identity of the local community but also ensures the endurance of Silat Buhun as a living heritage sustained by Islamic spiritual values amidst socio-cultural change.